2016
DOI: 10.1007/s13205-016-0366-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical markers during somatic embryogenesis in Silybum marianum L.

Abstract: In present report effects of explants type, basal media and plant growth regulators (PGRs) were tested for induction of indirect somatic embryogenesis in medicinally important plant Silybum marianum L. Leaf, petiole and root explants were exploited in vitro on B5 (Gamborg), SH (Schenk and Hildebrandt) and MS (Murashige and Skoog) media for induction of embryogenic callus followed by somatic embryogenesis. Highest callus induction frequency (76 ± 4.8 %) was recorded when petiole explants of in vitro derived pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…The augmentation of AgNPs to solid culture media was found encouraging for production of polyphenolics content in callus cells of C. tuberculata. The information on polyphenolics content in in vitro-based materials of Caralluma are still absent in the literature cited; however, various medicinal plant species are exploited for the production of polyphenolics content [36][37][38]. Khan et al [39] and Saeed et al [40] observed that elicitors and PGRs are not only involved in the process of morphogenesis but also fluctuate the pathways of secondary metabolism to release higher contents.…”
Section: Resultsmentioning
confidence: 99%
“…The augmentation of AgNPs to solid culture media was found encouraging for production of polyphenolics content in callus cells of C. tuberculata. The information on polyphenolics content in in vitro-based materials of Caralluma are still absent in the literature cited; however, various medicinal plant species are exploited for the production of polyphenolics content [36][37][38]. Khan et al [39] and Saeed et al [40] observed that elicitors and PGRs are not only involved in the process of morphogenesis but also fluctuate the pathways of secondary metabolism to release higher contents.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of chemical parameters can be used as a marker to assess somatic embryogenesis [14, 15]. Studies suggest that antioxidant enzymes such as catalase and ascorbate peroxidase play an important role in the growth and differentiation of plant cells and tissues and their high activities are associated with cell differentiation process [10, 16, 17].…”
Section: Resultsmentioning
confidence: 99%
“…The researchers observed that elimination of auxin from medium can lead to the continuation of somatic embryogenesis [8, 12, 13]. Measurement of chemical compositions such as contents of proline, protein, and antioxidant enzymes including catalase, ascorbate peroxidase, and peroxidase has been used as a marker to evaluate somatic embryogenesis in different studies [10, 14, 15]. Studies suggest that antioxidant enzymes such as catalase and ascorbate peroxidase play an important role in maturity and differentiation of plant tissues and their high activity affects cellular processes such as somatic embryogenesis [10, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The differential morphogenetic shifts exhibited by different explants at the same growth conditions may be linked with the genetic variability of the explant types (Abbasi et al 2016).…”
Section: Induction and Establishment Of Adventitious Rootsmentioning
confidence: 99%